Sifat Kimia dan Organoleptik Brownies Kukus dari Proporsi Tepung Mocaf dan Terigu - Sutrisno Adi Prayitno; Restu Tjiptaningdyah; Fadjar Kurnia Hartati (Agricultural Faculty, 2018)
The purpose of this research is to know the response of mocaf flour and wheat flour ratio to the chemical and organoleptic properties of steamed brownies cake. The research method used is experimental method, using Completely Randomized Design with 1 factor and 5 repetition, that are the ratio factor of mocaf flour and wheat flour are 5 levels, so the total replication becomes 25 times. The results showed that the ratio of mocaf and wheat flour did not have a significant effect on water content but had a very significant effect on crude fiber content. While the ratio of mocaf and wheat flour have no significant effect on organoleptic taste, color and flavor but have a very real effect on the tenderness of steamed brownies cake. The results of effectiveness test of mocaf and wheat flour efficacy ratio of 40:60 is the best treatment with the result value of 0.72 whereas the lowest treatment is the treatment of mocaf and wheat flour ratio of 100:0 with the result value of 0.37.